Measurement of line strengths in the Ã 2A' ← X˜2A" transition of HO2 and DO2. (November 2017) - Assaf, Emmanuel; Asvany, Oskar; Votava, Ondrej; Batut, Sébastien; Schoemaecker, Coralie; Fittschen, Christa
Highlights: The Ã 2 A' ← X ˜ 2 A" transition of HO2 and DO2 radicals have been measured by cw-Cavity Ring Down Spectroscopy. Absolute absorption cross sections have been determined for both radicals. Abstract: The absorption spectrum of the Ã 2 A' ← X ˜ 2 A" 000–000 band of HO2 and DO2 radicals has been measured in the range 6941–7077 cm −1 with a resolution of around 0.005 cm −1 . HO2 and DO2 radicals were generated from the reaction of Cl-atoms with CH3 OH and CD3 OD, respectively, whereby Cl-atoms were generated by pulsed photolysis of (COCl)2 at 248 nm. One time-resolved absorption curve was measured by cw-Cavity Ring Down Spectroscopy (cw-CRDS) for each wavelength. The relative absorption coefficient for each wavelength was then obtained from the ring down time τ, extrapolated to t = 0 s with respect to the photolysis pulse, and the ring down time τ0 before the photolysis pulse. Absolute absorption coefficients were quantified for several selected lines relative to a well characterized absorption line of HO2 at 6638.21 cm −1 by a second cw-CRDS absorption path. The maximum absorption cross section at 50 Torr Helium was for HO2 the transition N Ka Kc J = 11 0 11 11.5 ← 11 1 11 11.5 with σ7000.28 cm − 1 = 2.12 × 10 −19 cm 2 and for DO2 the doublet transition N Ka Kc J = 18 1 18 18.5 ← 18 0 18 18.5 and 18 1 18 17.5 ← 18 0 18 17.5 with σ7019.83 cm − 1 = 2.97 × 10 −19 cm 2 . The full spectrum has been very well reproduced by employing spectroscopic data from earlier works.